Effect of Fe Doping on Magnetic Behavior of SnO2 Nanoparticles for Spintronics Applications. (August 2019) - Sharma, Mayuri; Doila, S. N.; Kumar, Shalendra; Alvi, P. A.
Abstract: Doping of magnetic ion (Transition metal) in oxide based semiconducting material at nanoscale level serves a variety of spintronics based applications. In order to understand the influence of doping concentration of Fe ions on the magnetic behavior of semiconducting oxides, we have synthesized Fe doped tin oxide nanoparticles with 1 and 2% doping concentration via chemical co-precipitation method and then magnetic measurements have been taken through Superconducting quantum interference device (SQUID) at 5K and 300K temperatures for both the samples. Various magnetic quantities such as coercivity (Hc), saturation magnetization (Ms), remanent magnetization (Mr) have been extracted from the obtained hysteresis loops and found reduction in their values with increasing doping concentration which might corresponds to the tuning of oxygen defects created due to the substitution of dopant ions in the host lattice. In this way, our study can contribute to fulfill the necessity of ferromagnetism based applications such as data storage devices, gas sensors, communication, quantum computation etc.